William H. R. Wood, Digest of the Laws of California 334 (1861) - (:unkn) unknown (My University, 1861)
Art. 1904: Prohibited the display of any dirk, dirk-knife, Bowie knife, sword, sword cane, pistol, gun, or other deadly weapon in a threatening manner, or use of such weapon in a fight. Punishable by a fine of $100-500 or imprisonment for 1-6 months.
Keywords: BRANDISHING; DUELING